History and development of documentary production in Malaysia - Yasin, Megat Al Imran (2007)
The purpose of this paper is to unveil some of the history and development of documentary programme making in Malaysia, from the establishment of the Malaysian Film Unit (currently known as Filem Negara Malaysia) by the British colonials office in 1946 after the World War II until the period of commercialisation of television stations in Malaysia. The Malayan Film Unit was part of the Department of Information set up by the British government after the Second World War in 1946 that serve as propaganda tools to disseminate the government’s information. Therefore it is significant in this study to share the information about the British people involvement in setting up documentary film movement (as part of documentary film movement in Britain) in Malaysia (formerly known as Malaya).